Evaluasi Usability pada Aplikasi Glasgow Coma Scale (GCS) berbasis Android menggunakan Metode System Usability Scale (SUS) - Fajar Indra Kurniawan (Politeknik Kampar, 2024)
This study aims to evaluate the usability level of the Android-based Glasgow Coma Scale (GCS) application using the System Usability Scale (SUS) method. The Android-based application studied is Pemeriksaan GCS 1.0 by Creative Inspiring01. This application was chosen because it has a simple interface, is easy to use, and is available in Indonesian, which suits the needs of medical personnel. This study involved 30 ambulance officers who regularly perform GCS assessments during their duties. After using the application, participants were asked to complete the SUS questionnaire consisting of 10 Likert-scale statements. The data obtained were analyzed to calculate the average SUS score, which was then interpreted using three approaches: Acceptability Ranges, Grade Scale, and Adjective Rating. The results showed that the application received an average SUS score of 77.3, which falls into the Marginally Acceptable category and Grade C with an Excellent rating. Although the application was considered fairly good and acceptable, there are several areas for improvement, such as the user interface, application response speed, and customization settings.